Anti-Tumour Necrosis Factor Therapy for Inflammatory Bowel Diseases Do Not Impact Serious Infections after Arthroplasty. (26th September 2018) - Gregory, Martin H; McKinnon, Andrew; Stwalley, Dustin; Hippensteel, Kirk J; Loftus, Edward V; Ciorba, Matthew A; Olsen, Margaret A; Deepak, Parakkal
Abstract: Background and Aims: There is a paucity of data on the safety of joint replacement surgery in patients with inflammatory bowel disease [IBD], including those on tumour necrosis factor-alpha inhibitors [anti-TNF]. We explored the risk of serious infections in this population. Methods: A retrospective case-control study [2006–2014] was performed using the MarketScan Database. All patients aged 18–64 years with an International Classification of Diseases code for IBD and an IBD-specific medication, with ≥ 6 months of enrollment prior to hip, knee or shoulder replacement surgery, were included. Ten non-IBD controls were frequency-matched to each case on length of enrollment, year and the joint replaced. Primary outcome was serious infection [composite of joint infection, surgical site infection, pneumonia, sepsis] within 90 days of the operation. Cox proportional hazards models were used to assess the association of IBD and IBD medications with serious infection. Results: More patients with IBD [ N = 1455] had serious infections than controls [3.2% vs 2.3%, p = 0.04], but not after controlling for comorbidities (hazard ratio [HR], 1.3; 95% confidence interval [CI], 0.95–1.76). Among IBD patients, corticosteroids were associated with increased risk of serious infection [HR, 4.6; 95% CI, 2.2–9.8; p < 0.01] while anti-TNFs were not. Opioids were also associated with increased risk of infection [HR, 1.5; 95% CI, 1.2–1.8; p < 0.01]. Conclusions: After controlling for comorbidities, IBD patients were not at increased risk of serious infection following joint replacement. Corticosteroids, but not anti-TNFs or immunomodulators, were associated with increased risk of serious infections in IBD patients.